Measuring the Marginal Effective Tax Rate in Croatia, 2000–2024 - Bezeredi, Slavko (European Journal of Applied Sciences, 2025)
The analysis of marginal effective tax rate (METR) is particularly valuable in the context of labor markets and employment policy. High METR can reduce incentives for additional work or overtime, while lower rates or targeted tax allowances may encourage greater workforce participation. This paper aims to analyze the variations in the METR in Croatia from 2000 to 2024 across various household types, examining how changes in the tax and benefit system and wage growth over time have influenced METR trends. Additionally, a comparative assessment of METRs between Croatia and 22 EU countries that are also OECD members is conducted for 2024, evaluating Croatia’s position relative to other countries. Notably, Croatia's METR for a single average-wage earner stands at 38.9%, which is below the EU-OECD average of 41.6%, with the lowest rates observed in the Czech Republic and Slovakia, and the highest in the Netherlands and Belgium.